A Comparative Study of Chromium: Therapeutic Uses and Toxicological Effects on Human Health. Issue 3 (September 2022) - Ray, Anaiska; Jankar, Jayshri Sadashiv
Chromium is an essential trace element whose deficiency can cause impairment of glucose tolerance, growth and various biological functions. There are two isotopes of chromium-trivalent chromium and hexavalent chromium. Both the isotopes of chromium have quite different effects on the human body. The objective of this narrative review is to compile the different effects of the two isotopes of chromium and give a comprehensive analysis of the effects of hexavalent and trivalent chromium. Data from various studies across different forums were compared to provide a concrete analysis of the therapeutic and harmful effects of two isotopes of chromium on human health. Chromium plays a vital role in the biological functions of the body. It might be helpful in balancing the glycaemic levels, triglyceride levels and cholesterol levels in the body. Excessive intake of chromium is harmful for health. Overexposure to chromium can lead to carcinogenic effects. Consumption of an insufficient amount of chromium might not be adequate as well. Trivalent chromium can be quite beneficial if taken in proper quantities. Hexavalent chromium can cause cancer. Trivalent chromium is beneficial, while hexavalent chromium is harmful to human health.